2021
DOI: 10.1007/s00107-021-01739-6
|View full text |Cite
|
Sign up to set email alerts
|

Repeated thermo-hydrolytic disintegration of medium density fibreboards (MDF) for the production of new MDF

Abstract: Medium density fibreboards (MDF) are currently not recycled after service life, but various publications report on recycling by the disintegration of MDF using various techniques and the properties of obtained recovered fibres (RF). In this study, the main aim was to put back RF into the MDF manufacturing process as closed-loop recycling using repeated thermo-hydrolytic disintegration. Compared to previous studies, the focus was on the recycling of MDF with a relatively low F:U molar ratio (1.11). Urea–formald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
6
22
0
Order By: Relevance
“…The selected process parameters are consistent with the study carried out by Moezzipour, B. et al [39]. Other studies in the field show that at lower hydrolysis temperatures and similar process times, formaldehyde emissions in MDF panels fabricated with recycled fibers significantly increase [34]. That could be seen as circumstantial evidence of the incomplete disintegration of UF resins to amino compounds.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…The selected process parameters are consistent with the study carried out by Moezzipour, B. et al [39]. Other studies in the field show that at lower hydrolysis temperatures and similar process times, formaldehyde emissions in MDF panels fabricated with recycled fibers significantly increase [34]. That could be seen as circumstantial evidence of the incomplete disintegration of UF resins to amino compounds.…”
Section: Methodssupporting
confidence: 88%
“…With the selected hydrolysis regimes, 100% of the binder components remained in the recycled fibers. Lubis et al [34] found that only 33.5% of the UF resin components were present in recycled fibers after performing acid hydrolysis. Another study [39] corroborated these findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of WF boards, along with the chemical bonding provided by the pMDI binder, the wood fibers are interlocked with each other to form a stable structure. In addition, shorter and thinner fibers usually provide high internal bond strength [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher compression strength of WF boards can be explained by the higher glue effectiveness as well. Short and thin wood fibers have a great surface area and glue is utilized to a high extent [ 39 ].…”
Section: Resultsmentioning
confidence: 99%